Perancangan Sasaran Mutu Lembaga Sertifikasi Personel Dengan Balance Scorecard - Sumaedi, Sik; Yarmen, Medi (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
ISO/IEC 17024 directs Bodies Operating Certification of Person to adopt documented quality management system according to ISO 9001:2008. Bodies Operating Certification of Person that implement ISO 9001 documentation system should have quality objective. Quality objective is wished to be appropriated with institution performance indicators.Therefore, when quality objective is achieved, the institution performance is also good. The problem is quality objective in ISO 9001 is generally explained. This condition pushes Bodies Operating Certification of Person to identify the appropriate quality objective framework. Balance Score Card, a strategic performance measurement management framework that consist of 4 perspectives (financial, customer, internal process, learning and growth) that effectively proven could be solution for that problem. This research is to implement Balance Score Card performance management framework in Bodies Operating Certification of Person’s quality objective. This research is important considering there is no previous research that implement Balance Score Card in a Bodies Operating Certification of Person. The research result shows Balance Score Card based quality objective design with totally 12 quality objectives that consist of 1 financial perspective’s quality objective, 5 customer perspective’s quality objectives, 3 internal process perspective’s quality objectives, and 3 learning and growth perspective’s quality objectives.